Indonesian national assessment support: Can RE-STEM Android app improve students’ scientific literacy skills? - Bambang Subali; Ellianawati Ellianawati; Zulfatul Faizah; Mohamad Sidiq (Institute of Advanced Engineering and Science, 2023)
The Indonesian National Assessment set by the government is in line with the Program for International Student Assessment (PISA) assessment which includes students’ scientific literacy skills for a 21st century education succeeds. This study determined the increase in students’ scientific literacy skills through ethnoscience, science, technology, engineering, mathematics or ethno-STEM learning assisted by RE-STEM App. A quasi-experimental design with the type of one-group pretest-posttest design was used to obtain data from the treatment. There were 102 students involved by purposive sampling technique from a 338 population of grade 8 students in a rural secondary school in Central Java, Indonesia. RE-STEM App involves four themes of Indonesian cultures as learning resources, namely tarutu, tin-telephone, calung, and bird whistle. This study revealed that students’ scientific literacy skills increased by 61.33% in the medium category in general, also in each aspect. Research data indicate that the RE-STEM App has supported teachers to improve students’ scientific literacy skills. By applying ethno-STEM through RE-STEM App, teachers can help students to investigate the science concepts in ethnoscience. This strategy proved that ethnoscience aspect can be an important factor in developing students’ scientific literacy skills.